The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/ijpo.12285
|View full text |Cite
|
Sign up to set email alerts
|

Waist‐to‐height ratio as a risk marker for metabolic syndrome in childhood. A meta‐analysis

Abstract: Measuring WtHR may be considered in regular health checks of children and adolescents, as it can measure cardiovascular risk regardless of the degree of general obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 44 publications
1
31
0
2
Order By: Relevance
“…Based on the idea "keep your WC to less than half your height," the cutoff of 0.5 was established [20]. However, different studies have demonstrated that this cutoff point has a low accuracy to diagnose metabolic abnormalities [28]. Based on the data from the NHANES, the cutoff of 0.60 has been proposed as an effective tool for classifying the metabolic risk among obese children and adolescents [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the idea "keep your WC to less than half your height," the cutoff of 0.5 was established [20]. However, different studies have demonstrated that this cutoff point has a low accuracy to diagnose metabolic abnormalities [28]. Based on the data from the NHANES, the cutoff of 0.60 has been proposed as an effective tool for classifying the metabolic risk among obese children and adolescents [26].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have proposed that WtHR is more sensitive than other anthropometric parameters as an early warning of health risks [11] and seems to be an effective indicator of central adiposity [26]. Children with a high level of WtHR have four times more risk of developing MetS [28]. Moreover, it is simple to measure and calculated because it does not require gender-and age-specific centiles, but the threshold of WtHR ≥ 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WHtR is regarded as one of the most potent markers of cardiometabolic risk in children and adolescents. In fact, Ochoa‐Sangrador and Ochoa‐Brezmes concluded that WHtR should be measured in regular health checks in this population, as it can measure cardiovascular risk regardless of the degree of general obesity. In their meta‐analysis if 31 studies, these authors showed a pooled AUC of 0.76 for boys and girls for MetS, which is slightly lower that the AUC observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, WC has been questioned for not considering height and hip circumference, and thus, the waist‐to‐hip ratio (WHR) and waist‐to‐height ratio (WHtR) emerged as parameters of clinical interest to evaluate adiposity and predict the cardiovascular risk. However, whereas WHtR has revealed as a potent marker of MetS in childhood, inconclusive results were obtained for WHR …”
Section: Introductionmentioning
confidence: 99%